Effects of hepatitis B virus infection and strategies for preventing mother-to-child transmission on maternal and fetal T-cell immunity - Lu, Huihui; Cao, Weihua; Zhang, Luxue; Yang, Liu; Bi, Xiaoyue; Lin, Yanjie; Deng, Wen; Jiang, Tingting; Sun, Fangfang; Zeng, Zhan; Lu, Yao; Zhang, Lu; et al. (Frontiers in Immunology, 2023)
One of the most common routes of chronic hepatitis B virus (HBV) infection is mother-to-child transmission (MTCT). Approximately 6.4 million children under the age of five have chronic HBV infections worldwide. HBV DNA high level, HBeAg positivity, placental barrier failure, and immaturity of the fetal immune are the possible causes of chronic HBV infection. The passive-active immune program for children, which consists of the hepatitis B vaccine and hepatitis B immunoglobulin, and antiviral therapy for pregnant women who have a high HBV DNA load (greater than 2 × 105 IU/ml), are currently two of the most important ways to prevent the transmission of HBV from mother to child. Unfortunately, some infants still have chronic HBV infections. Some studies have also found that some supplementation during pregnancy can increase cytokine levels and then affect the level of HBsAb in infants. For example, IL-4 can mediate the beneficial effect on infants’ HBsAb levels when maternal folic acid supplementation. In addition, new research has indicated that HBV infection in the mother may also be linked to unfavorable outcomes such as gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, and premature rupture of membranes. The changes in the immune environment during pregnancy and the hepatotropic nature of HBV may be the main reasons for the adverse maternal outcomes. It is interesting to note that after delivery, the women who had a chronic HBV infection may spontaneously achieve HBeAg seroconversion and HBsAg seroclearance. The maternal and fetal T-cell immunity in HBV infection is important because adaptive immune responses, especially virus-specific CD8 T-cell responses, are largely responsible for viral clearance and disease pathogenesis during HBV infection. Meanwhile, HBV humoral and T-cell responses are important for the durability of protection after fetal vaccination. This article reviews the literature on immunological characteristics of chronic HBV-infected patients during pregnancy and postpartum, blocking mother-to-child transmissions and related immune mechanisms, hoping to provide new insights for the prevention of HBV MTCT and antiviral intervention during pregnancy and postpartum.